Investigation of Biological, Scolicidal and Antimicrobial Activities of the Solvent Extracts Components of Cystoseria barbata Seen off Sinop Province - Karaman, Ulku; Yucel, Tayyibe Beyza; Cebeci, Tugba; Arici, Yeliz Kasko; Yucel, Murat; Korkmaz, Busra (Indian Journal of Pharmaceutical Education and Research, 2022)
Aim/Background: Seaweeds are unicellular or multicellular vegetative organisms and have a wide distribution. Their antitumoral, antiviral, antifungal, insecticidal, cytotoxic, and phytotoxic and antiproliferative activities were determined. The aim of the study was to investigate the biological, antimicrobial and scolicidal activities of Cystoseria barbata (C. barbata). Materials and Methods: Cystoseria barbarata was collected in appropriate quantities. Some of them were extracted by water vapor distillation, and some of them were extracted by Soxhlet extraction with hexane, dichloromethane, chloroform and methanol. Antimicrobial and scolicidal effects were investigated in the extracts. For the scolicidal effect, the difference between the hours at each dose for each solution and the difference between the doses at each hour were compared by ANOVA. The values of lethal concentration doses (LD50 and LD90) were calculated using probit analysis. Results: The antimicrobial activities of the solutions of the solvent extracts of Cystoseria barbarata in DMSO against Acinebacter baumannii ATCC BAA-747, Bacillus cereus ATCC 10876, Bacillus megaterium DSM32, Bacillus subtilis ATCC 6633, Candida albicans ATCC 10231, Citrobacter freundii ATCC 43864, Enterococcus faecalis ATCC 29212, Escherichia coli ATCC 25922, Escherichia coli ATCC 36218, Enterobacter aerogenes ATCC 13048, Klebsiella pneumoniae ATCC 13883, Methicillin Resistant Staphylococcus aureus ATCC 67101, Proteus mirabilis ATCC 4307, Pseudomonas aeruginosa ATCC 27853, Pseudomonas aeruginosa ATCC 9027, Salmonella typhimurium ATCC 14028, Staphylococcus aureus ATCC 29213, Staphylococcus aureus ATCC 25923 and Staphylococcus epidermidis ATCC 12228 micro-organisms were determined. In the scolicidal effect, no change was observed in the administration of hexane extracts with respect to the duration. However, a statistically significant change was observed in the number of parasites in terms of time in others. Conclusion: It was determined that the solvent extracts of C. barbarata may have bactericidal and scolicidal effects. It is suggested that experimental studies required to investigate the effects of this algae and use it in living cells should be conducted.
Keywords: Cystoseria barbarata; Scolicidal; Antimicrobial activity; Lethal dose; Probit; analysis